Pengaruh Pembelajaran E-Learning Terhadap Efektifitas Guru Mata Pelajaran Di SMTK Kota Kupang - Desry Taneo (Institut Agama Kristen Negeri Kupang, 2021)
This research aims to determine the effect of e-learning learning on the effectiveness of subject teachers in Christian Theology Middle School, Kupang City. This study uses a quantitative approach. The analysis technique used is by using linear regression analysis techniques. Then the results obtained are Reliability test results for variables X and Y, all of which are reliable because of the value of Cronbach, s Alpha> r Table (0.05). After the reliability test, the researcher conducted a descriptive statistical test and continued with the normality test. In the residual normality test, the data is normal because the sig value is 406> 0.05. Followed by the normality analysis test, the researchers continued to the linearity analysis test. Based on the results of the linearity test, it was known that the sig. deviation linearity value was 0.189. Because of the sig. 0.189.> 0.05, then it can be concluded that Ho is rejected and Ha is accepted. This means that there is a linear relationship between e-learning learning and subject teachers' effectiveness in the last analysis test, namely hypothesis testing. Based on the results of the correlation test, it is known that the sig. Value is 0.00. Because of the sig. 0.00. <0, 05 it can be concluded that Ho is rejected and Ha is accepted. This means that there is a significant influence between e-learning learning and the effectiveness of subject teachers. With the reason that the value of R (correlation) 0.989> 0.05 with the influence (R square) 0.979 or 97.9%. Thus, the hypothesis testing in this study produces Ha.